Exploring the translation equivalences in translating ironic expressions in Arabic newspaper editorials - Al-Shehabat, Kholud Mahmoud (Linguistics and Culture Review, 2021)
The current study explores the translation equivalences in translating ironic expressions in Arabic newspaper editorials and to what extent Jordanian respondents can capture the ironic message(s) in the original text. Several sarcastic and ironic expressions are randomly selected from Al-Zoubi’s corner in Al-Rai daily. They have been given to 20 M.A. students at Jadara University; to translate from Arabic into English. The findings indicate that the students employed various translation techniques, namely, word-for-word, literal translation, functional equivalence, and ideational equivalence methods, to render the meaning of various ironic expressions in Arabic newspaper editorials.